Effects of Debt Recovery Techniques on Performance of Small and Medium Enterprises in Embu Town - Ndumi Peter, Rachael (University of Embu, 2020)
The purpose of this research was to examine the effect of debt recovery techniques on financial performance of SMEs. The study objectives were to examine the effect of account transactions, guarantors and the effect of collateral retention on performance of SMEs in Embu town. The study was guided by customer-supplier relationship theory. The research design adopted a descriptive survey design. The study was conducted on SMEs within Embu County. The target population consisted of 350 employees from the credit and management department of selected SMEs. The study used purposive sampling technique to select 20SMEs. The research preferred the secondary data. The data collected in the study was analysed by the use of descriptive statistics and inferential statistics. This includes the use of descriptive statistical methods to analyse data consisting of frequency, mean and standard deviation. The relationship between variables was done using multiple linear regression models. Tables were used to present the results. Based on the findings of the study, the study recommended among others that the SMEs should review account histories as suggestion tools for accounts such as savings accounts, investment accounts and also retirement accounts for additional information on customer ability to repay their loans. The study suggests that same study be done in other enterprises not considered in this study to allow generalizations and also provide rich advances for future studies. Further research is also required to study the factors determining debt recovery in other enterprises both medium and large.